Trpc1 Ion Channel Modulates Phosphatidylinositol 3-Kinase/Akt Pathway during Myoblast Differentiation and Muscle Regeneration - Zanou, Nadège (American Society for Biochemistry and Molecular Biology, 2012)
We previously showed in vitro that calcium entry through Trpc1 ion channels regulates myoblast migration and differentiation. In the present work, we used primary cell cultures and isolated muscles from Trpc1(−/−) and Trpc1(+/+) murine model to investigate the role of Trpc1 in myoblast differentiation and in muscle regeneration. In these models, we studied regeneration consecutive to cardiotoxin-induced muscle injury and observed a significant hypotrophy and a delayed regeneration in Trpc1(−/−) muscles consisting in smaller fiber size and increased proportion of centrally nucleated fibers. This was accompanied by a decreased expression of myogenic factors such as MyoD, Myf5, and myogenin and of one of their targets, the developmental MHC (MHCd). Consequently, muscle tension was systematically lower in muscles from Trpc1(−/−) mice. Importantly, the PI3K/Akt/mTOR/p70S6K pathway, which plays a crucial role in muscle growth and regeneration, was down-regulated in regenerating Trpc1(−/−) muscles. Indeed, phosphorylation of both Akt and p70S6K proteins was decreased as well as the activation of PI3K, the main upstream regulator of the Akt. This effect was independent of insulin-like growth factor expression. Akt phosphorylation also was reduced in Trpc1(−/−) primary myoblasts and in control myoblasts differentiated in the absence of extracellular Ca(2+) or pretreated with EGTA-AM or wortmannin, suggesting that the entry of Ca(2+) through Trpc1 channels enhanced the activity of PI3K. Our results emphasize the involvement of Trpc1 channels in skeletal muscle development in vitro and in vivo, and identify a Ca(2+)-dependent activation of the PI3K/Akt/mTOR/p70S6K pathway during myoblast differentiation and muscle regeneration.